Superparamagnetic iron oxide nanoparticle-loaded polyacrylonitrile nanofibers with enhanced arsenate removal performance. Issue 5 (5th September 2016) - Morillo, D.; Faccini, M.; Amantia, D.; Pérez, G.; García, M. A.; Valiente, M.; Aubouy, L.
Abstract : Novel nanocomposite sorbents of superparamagnetic iron oxide nanoparticles (SPION) supported onto electrospun polyacrylonitrile nanofibers were synthesized by a simple and scalable method. Abstract : Novel nanocomposite sorbents of superparamagnetic iron oxide nanoparticles (SPION) supported onto electrospun polyacrylonitrile nanofibers were synthesized by a simple and scalable method. The influence of both nanofiber size and SPION loading on As(v ) adsorption capacity was studied and optimization was conducted. A maximum uptake capacity of 32.5 mmol As(v ) per gram SPION in batch mode tests using an extremely low loading of only 2.9 mg of SPION per gram of adsorbent was achieved. This represents a remarkable improvement of 36 times compared with SPION in suspension. The optimal material was tested in continuous flow operation mode, reaching an adsorption capacity of 851.7 mg As(v ) per gram of adsorbent at pH 3.8. It is also demonstrated that the new adsorbents can retain high performance when tested under real conditions using polluted wastewater from a lixiviation dump containing a large amount of competing anions (Cl − and F − ) and interfering cations (K +, Na +, Mg 2+, and Ca 2+ ). Furthermore, there was no release of nanoparticles observed during the operation and the spent porous material can be compressed, generating a small amount of solid waste that can be easily treated or stored.